Facilitating workplace learning and change: Lessons learned from the lectores in pre-war cigar factories. Issue 5 (13th July 2015) - Germain, Marie-Line; Grenier, Robin S.
Abstract : Purpose: – This study aims to describe the lectores (readers) who read the world news and works of literature to workers in pre-World War II cigar factories in Tampa, Florida, and in New York City. The paper addresses the need for more examination of some neglected aspects of workplace learning by presenting a more critical approach to workplace learning as a form of social change. It also focuses on the importance of the lectores' role as facilitators of workplace learning and leaders of change. Design/methodology/approach: – The paper is based on a qualitative analysis of archival data from libraries and research centers located in New York City and in Miami, Florida. Findings: – Through the lectores, cigar factories were a place where workplace learning, organizational and social change occurred daily. As leaders, the lectores were radical agents of change and created affordances that shaped the factory workers' workplace and personal learning. The discussion explores the dynamics between the lectores and the cigar workers. Practical implications: – Findings from this study demonstrate that developing employees is not limited to elevating their knowledge and skills needed to increase productivity and organizational performance. As self-actualized employees are better contributors to organizations, they, along with facilitators of learning, must care about what workers intrinsically need and explicitly demand. The findings speak to the multifaceted nature of workplace learning, one that encompasses skill acquisition and one that transforms workers. In essence, learning facilitators elicit change. Originality/value: – The research literature on workplace learning in the early part of the twentieth century in the USA is rare. This historical data-driven examination of the lectores and their role in factories presents a unique opportunity to focus on issues of social justice that are largely absent from human resource development discourse.